Neuroscience-Based Higher Order Thinking Skills Development Model for Religious Moderation - Suyadi; Hairiyah (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
Since the emergence of the idea of Islamization of science by Al-Faruqi from the Middle East to integration-interconnection by Amin Abdulla in Indonesia, there has been no institution that has officially developed this idea institutionally or institutionalized it in education. However, the birth of a new concept of Trensains by Agus Purwanto has been officially institutionalized through an educational institution explicitly named the Trensains school. The presence of trensains schools answers the problem of 21st-century Islamic education from Low Order of Thinking Skills (LOTS), which risks spreading radical Islamic ideology, to Higher Order of Thinking Skills (HOTS), which has the potential to strengthen religious moderation. This study investigates the development of HOT in Islamic education to strengthen religious moderation at Trensains Tebuireng High School in Jombang, East Java, Indonesia. The research method used is qualitative research of the case study type. Data collection techniques were carried out through observation, interviews, and documentation. The informants for this study were the principal and Islamic education teachers. Data analysis was carried out through display, reduction, and interpretation. The results of the study show that Trensains differs from science development in modern Islamic boarding schools, which aim to produce scholars who are literate in science, but rather integrates Islamic boarding schools and science in schools to produce Islamic Muslim scientists. Trensains High School develops HOTS Islamic education through “Integrative Interaction between Islam and Science” learning. On the other hand, this school also maintains NU-based Aswaja learning as the driving force for religious moderation. It turns out that the interaction between Islam and science in Aswaja learning has become a new model of HOTS Islamic Religious Education and strengthens religious moderation.